Application Of The Peer Teaching Method In Learning Arabic Language Maharoh Kalam - Zariah, Ainun; Hasan, Mohammad Abdul Kholiq (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to describe the implementation of the peer tutoring (peer teaching) method in learning Arabic, particularly in speaking skills (maharah kalam), among seventh-grade students at SMPI PK Muhammadiyah Delanggu. This research was motivated by students’ low speaking proficiency, differences in prior Arabic learning experiences, fear of making mistakes when speaking, and the lack of varied teaching methods that resulted in passive learning and low student confidence. The peer tutoring method was chosen because it allows students to learn through peers who have higher competency, thereby creating a learning atmosphere that is more familiar, communicative, and collaborative.This study employed a descriptive qualitative approach, using observation, interviews, and documentation as data collection techniques. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, and validated using triangulation, audit trail, and member checking. The data sources consisted of the school principal, the Arabic language teacher, and seventh-grade students.The findings indicate that the implementation of peer tutoring helps students become more active, confident, and better able to understand Arabic learning materials. Peer tutoring proved to be effective because students feel more comfortable asking questions and discussing with their peers. This method also reduces teacher dominance, enhances two-way interaction, and helps bridge the gap between students who have and have not previously studied Arabic. Thus, peer tutoring can serve as an effective alternative instructional strategy to improve students’ Arabic speaking skills.